Optimal order policy for a two-stage newsvendor problem with forecast updates and order lead times - Rodriguez, Federico Jose S. (2011)
The newsvendor problem is a single-period inventory problem where the newsvendor id faced with the task of decif=ding an order quantity that would minimize the combined cost of overage and underage. This problem typically arises with products that easily become expired or outdated like food and other perishables, clothing, newspapers and seasonal items such as cards, pins and ornaments.